Starvation-induced autophagy is up-regulated via ROS-mediated ClC-3 chloride channel activation in the nasopharyngeal carcinoma cell line CNE-2Z. Issue 9 (7th May 2019) - Zheng, Yanfang; Chen, Zhanru; Gu, Zhuoyu; Yang, Xiaoya; Yu, Meisheng; Zhao, Chan; Lin, Jiawei; Xu, Peisheng; Zhu, Linyan; Jacob, Tim J. C.; Peng, Shuang; Chen, Lixin; et al.
Abstract : Nutrient deficiency develops frequently in nasopharyngeal carcinoma cell (CNE-2Z) due to the characteristics of aggregation and uncontrolled proliferation. Therefore, starvation can induce autophagy in these cells. Chloride channel 3 (ClC-3), a member of the chloride channel family, is involved in various biological processes. However, whether ClC-3 plays an important role in starvation-induced autophagy is unclear. In this study, Earle's balanced salt solution (EBSS) was used to induce autophagy in CNE-2Z cells. We found that autophagy and the chloride current induced by EBSS were inhibited by chloride channel blockers. ClC-3 knockdown inhibited the degradation of LC3-II and P62. Furthermore, when reactive oxygen species (ROS) generation was suppressed by antioxidant N -acetyl-l -cysteine (L-NAC) pretreatment, EBSS-induced autophagy was inhibited, and the chloride current was unable to be activated. Nevertheless, ClC-3 knockdown had little effect on ROS levels, indicating that ROS acted upstream of ClC-3 and that both ROS and ClC-3 participated in EBSS-induced autophagy regulation in CNE-2Z.